Determination of prevalence, characteristics, management and related factors for pain in the older adults: pain among nursing home residents - Okuyan Canan Birimoglu; Eloranta Sini; Elhouda; Halaweh Nour (Brazil, 2022)
This study aimed to determine pain assessment approaches and pain management strategies in elderly people in a nursing home. The cross-sectional-descriptive study sample consisted of 147 older adults living in a nursing home in Turkey in 2019. They all agreed to participate in the study (n = 147); however, as our research was about older adultswith pain problems, the study was completed with a total of 108 older adultsexperiencing pain problems. The participants' average age was 73.60 ± 6.97 years. Geriatric pain scale scores were higher for women aged 75 years and over, those who had a chronic disease and those who received analgesics, and there was a statistically significant difference between the mean scores (p < 0.05). Nurses must pay attention to pain assessment and management in nursing homes because of the adverse effects of pain on older adults' health status, vital functions, and well-being.